Hubungan Strategik antara Pemasaran dan Kesetiaan Pengguna di Telekom Malaysia - Suhaida Herni, Suffarruddin (2010)
This research explores the impact of relationship marketing on customer loyalty in telecommunication sector. A survey of users of products and services in Telekom Malaysia was conducted to determine the significance and influence of the underpinnings of the relationship marketing such as trust, commitment, communication and conflict handlings on costumer' loyalty in the telecommunication sector. A total of 128 usable questionnaires were obtained from total of 150 questionnaires distributed. The flndings shows that the four(4) variable namely trust, commitment, communication and conflict handling, were important in determining and influencing customer' loyalty. Since the results of the research showed that customer' loyalty is related to trust, commitment, communication and conflict handling factors, therefore Telekom Malaysia need to consider these factors and provide the right tenant mixes, services, and other facilities that are essential for attracting customer.